Influence of fabrication method on the marginal fit of temporary restorations - Thaís Cristina Mendes RODRIGUES; Caio Cesar Dias RESENDE; Guilherme Faria MOURA; Fábio Henrique de Paulo Costa SANTOS; Gustavo MENDONÇA; Karla ZANCOPE; Flávio Domingues NEVES (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract Computer-aided manufacturing (CAM) technology allows the use of different manufacturing techniques. This in vitro study aimed to evaluate the marginal fit of temporary restorations manufactured using conventional chairside methods, milling, and three-dimensional printing. Fifteen 3-element temporary restorations specimens were produced and categorized into three groups: non-digital, obtained using the conventional chairside method (GC); milled (GM); and three-dimensionally printed (GP). Marginal fit was assessed using scanning electron microscopy (SEM) performed under two conditions: one with only the central screw tightened, and the other with all three screws tightened. Horizontal misfit values were categorized as over-, equal-, and under-extended and qualitatively analyzed. Statistical analysis was performed using the Tukey-Kramer test (α=0.05). In the vertical assessment, three-dimensionally printed restorations demonstrated greater misfit than restorations obtained by milling and the conventional chairside method (P<0.05). In the horizontal assessment, the misfit in the GP group was significantly higher than that in the GM and GC groups. Restorations obtained using the conventional chairside method and milled provisional restorations showed more favorable results than three-dimensionally printed restorations.